Development of P5 Learning Module Theme Ecoprint in Middle School - Hakiki, Nurul; Ahmad, Abd Aziz; Irfan, Irfan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The study's goal is to create a learning module project (P5) with an ecoprint theme to improve character in the application of independent dimensions and creative dimensions of students. This study uses research and development (R&D) and the 4D model scheme. The development of this 4-D model involved the steps of defining, designing, developing, and disseminating. Public Middle School 7 Makassar served as the study's site. The results of the study indicated that the assessment of the overall module by material experts obtained a value of 9.8 with an average of 4.9 with the description